MENUJU UMKM BERKELANJUTAN: INTEGRASI DIGITALISASI AKUNTANSI, KOMPETENSI SDM, DAN PENGELOLAAN KEUANGAN: TOWARDS SUSTAINABLE MSMES: INTEGRATING ACCOUNTING DIGITALIZATION, HUMAN RESOURCE COMPETENCE, AND FINANCIAL MANAGEMENT - Aulia, Yesi Rahma; Rizki, Novia (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
This study investigates the influence of accounting digitalization, human resource (HR) competence, and financial management on the sustainability of Micro, Small, and Medium Enterprises (MSMEs). Using a quantitative approach, data were collected through purposive sampling involving 126 MSMEs across five cities and districts on Lombok Island, Indonesia. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that accounting digitalization, HR competence, and financial management each have a significant and positive impact on MSME sustainability. These results highlight the importance of digital integration, strategic HR development, and sound financial practices as essential components in ensuring business resilience and long-term viability. The study contributes to the growing body of research on MSME sustainability and offers practical insights for policy makers, business practitioners, and development agencies seeking to foster sustainable entrepreneurship in emerging markets.